Isolation and characterization of non-O157 Shiga toxin-producing Escherichia coli (STEC) isolated from retail ground beef in Santiago, Chile. (October 2018) - Toro, Magaly; Rivera, Daniel; Jiménez, María Fernanda; Díaz, Leonela; Navarrete, Paola; Reyes-Jara, Angélica
Abstract: Shiga toxin-producing Escherichia coli (STEC) is one of the main cause of foodborne disease worldwide, but isolation rates or characteristics of this bacteria from ground beef in Chile are unknown. The present study aimed to isolate and characterize non-O157 STEC from ground beef sold at retail in the city of Santiago, Chile. We analyzed 430 ground beef samples for the presence of STEC, and isolated the microorganism in 10% of samples (43/430). We obtained 56 isolates from the 43 positive samples; 55 of these (98.2%) fermented sorbitol. Most isolates (98.2%; 55/56) showed β-glucoronidase activity, and only six (10.7%; 6/56) were resistant to tellurite. Among the virulence factors studied ( stx 1, stx 2, eae, and hlyA ), stx 2 was the only virulence factor in 41% of the isolates (23/56), whereas 10.7% (6/56) of isolates carried a combination of three virulence factors ( stx1 + stx2 + hlyA ). None of the isolates carried the gene eae . Finally, isolates were neither serogroups O157 nor "big six". In conclusion, ground beef sold in Santiago, Chile is contaminated with STEC; however, further studies are required for understanding their virulence potential. Highlights: STEC was isolated from 10% of ground beef samples obtained in Santiago, Chile. Most strains carried stx 2 as their main virulence factor. STEC isolates did not carry the virulence gene eae but some carried hlyA . STEC serogroups O157 and "big six" were absent from the beef samples analyzed. Most isolates were sorbitol+, β-glucoronidase +, and susceptible to tellurite.